2007
DOI: 10.1111/j.1524-475x.2006.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin peptide Chrysalin® stimulates healing of diabetic foot ulcers in a placebo‐controlled phase I/II study

Abstract: Thrombin and thrombin peptides play a role in initiating tissue repair. The potential safety and efficacy of TP508 (Chrysalin) treatment of diabetic foot ulcers was evaluated in a 60-subject, prospective, randomized, double-blind, placebo-controlled phase I/II clinical trial. Chrysalin in saline or saline alone was applied topically, twice weekly, to diabetic ulcers with standardized care and offloading. A dose-dependent effect was seen in the per-protocol population where 1 and 10 mug Chrysalin treatment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…We have shown previously that ASCs differentiated into vascular cells when injected into infarcted hearts [34]. In light of previous reports that TP508 promotes wound healing [12,13,14,15,16,17,18], our findings suggest that the beneficial effect of TP508 may be mediated by stem cells. To this end, it has been shown that autologous mesenchymal stem cells increase vascularity and reduce wound size of nonhealing diabetic ulcer [35].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…We have shown previously that ASCs differentiated into vascular cells when injected into infarcted hearts [34]. In light of previous reports that TP508 promotes wound healing [12,13,14,15,16,17,18], our findings suggest that the beneficial effect of TP508 may be mediated by stem cells. To this end, it has been shown that autologous mesenchymal stem cells increase vascularity and reduce wound size of nonhealing diabetic ulcer [35].…”
Section: Discussionmentioning
confidence: 50%
“…To this end, it has been shown that autologous mesenchymal stem cells increase vascularity and reduce wound size of nonhealing diabetic ulcer [35]. Importantly, a recent report showed that TP508 also stimulates healing of diabetic foot ulcers in a placebo-controlled phase I/II study [18]. It would be interesting to find out whether the beneficial effects of TP508 on diabetic ulcer are mediated by endogenous stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many of the serine proteases, for example, thrombin, downstream of FVIIa in the coagulation cascade elicit intracellular signaling, which regulates gene transcripts that are involved in wound healing (38). For example, administration of a 23-residue peptide derived from thrombin has been shown to accelerate wound repair (39), and enhancement of TF expression via gene transfer in wounds in diabetic mice restored the delayed wound closure times found in these mice to those of nondiabetic mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of doxycycline may have benefit. A thrombin peptide, chrysalin, has shown some evidence of improve-ment in wound healing (23). Topical adenosine agonists may improve wound healing, as neutrophil adenosine A2 receptors inhibit phagocytosis and secretion of inflammatory molecules and reduce oxidative stress, with these agents potentially increasing IL-10 secretion by monocytes, leading to anti-inflammatory effects and enhanced platelet aggregation.…”
Section: Stress and Woundmentioning
confidence: 99%